Effect of native and modified starches on nutritional and physiological performance of wild juveniles of red grouper (Epinephelus morio) - Castillo, Ana; Callejas, Leticia; Álvarez-González, Carlos Alfonso; Maldonado, Carlos; Cuzon, Gerard; Gaxiola-Cortés, Martha Gabriela (Ecosistemas y Recursos Agropecuarios, 2018)
The aim of this study was to evaluate carbohydratesutilization by wild red grouper Epinephelus morio.Juveniles were fed during 93 d on a selection of starches: native raw cornstarch (RCS), waxy cornstarch (WCS), raw potato starch (RPS) and gelatinized potato starch (GP) at 20% inclusion level. The best growth was obtained in fish fed cornstarch either native raw of waxy cornstarch (p0.05), whereas glycogen content increased up to 200 mg g-1with waxy cornstarch. Specific activity of a-glucosidase and α-amylase remained stable (p>0.05). Hepatic glycolytic enzymes increased with raw native and waxy cornstarch (p